Nomura Group : trading with privileged information - Oji, Chijioke; Makin, Viola, 1952- ([London] : SAGE, 2016)
In late March 2012, the Securities Exchange and Surveillance Commission (SESC), the investigative unit of the Japanese Financial Services Authority (FSA), confirmed that Nomura Securities Co., Ltd (NSC) - a subsidiary of Nomura Holdings, Inc. - had been involved in insider trading. On at least three occasions, before official announcements for share issues were made, employees at NSC leaked confidential information on securities offerings that the firm underwrote, with the aim of stimulating market demand for the shares. While trying to repair its tarnished reputation, the company faced hefty fines from the Japanese financial regulators.
Originally Published in: Oji, C., & Makin, V. (2013). Nomura Group: Trading with Privileged Information. WBS-2013-12. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Nomura Group; Insider trading in securities -- Japan -- Case studies; Banks and banking -- Corrupt practices -- Case studies; Business ethics -- Case studies